DAVE PELZER ’S PS YCHOLOGYCAL CONDITION AS A CHILD ABUS E VICTIM IN DAVE PELZER ’S A CHILD CALLED IT - -, SAHRUMAN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Parents should  provide protection and  basic  need  for their children.  A child who does not get the basic needs and gets torture from the parents will be in unstable     psychological        conditions.                 This                    skripsi focuses               on            children’s psychological condition after being tortured by his mother. The purpose of this research is to analyze Dave’s psychological condition as a child abuse victim in Dave Pelzer’s A Child Called It. Psychological approach is used in analyzing this novel because every torture done by Dave’s  mother gives  negative effects to Dave’s psychological condition. The result of this research shows that Dave suffers from some abuses such as physical abuse, emotional abuse, and neglect. Those abuses affects his psychological  conditions  in  the   forms  of  lacking  trust  on  others,   having difficulties   in  making   friends,   feeling   worthless  and  damaged  and   facing difficulties in managing emotion. The writer concludes that family especially mother has a big influence on a child’s psychological condition.  So,  a  mother  has  to  pay attention  to  their children’s health and psychological condition.     Key words: child abuse, types of child abuse, effects of child abuse, child abuse